SIGNIFIKANSI KEPEMIMPINAN MUSA TERHADAP GURU PENDIDIKAN AGAMA KRISTEN DALAM MENGAJAR - Gulo, Rezeki Putra (Edukasi : Jurnal Pendidikan Agama Kristen, 2022)
The leadership of Moses has given many examples that today's believers should emulate, especially teachers of Christian education. His loyal attitude in leading God's sheep out of Egypt to the promised land has marked him that he deserves to be a role model. Thus Christian teachers are encouraged to be able to have a soul that is so loyal in teaching students to know the truth. The method used by the author in writing this article is a qualitative method, namely library research. The author's conclusion about the significance of Moses' leadership on Christian religious education teachers in teaching is that today's Christian teachers want to have an attitude of loyalty, obedience, honesty, and intimacy to God in teaching and patience with the various pressures they face, just like Moses when he led God's people came out of Egypt to the promised land.